A Comparative Study on Use of Manual Versus Digital Method using Mobile Application for Cephalometric Measurements - Shrestha, Raju; Kandel, Santosh (Orthodontic Journal of Nepal, 2020)
Introduction: Various computer software and smartphone applications have been developed for digital cephalometric analysis with ease and in short time. The objective of this study was to compare linear and angular cephalometric measurements obtained, and cephalometric tracing duration between smartphone application tracing (app method) and conventional tracing (manual method) methods. Materials & Method: 35 digital Lateral cephalometric radiographs of patient who came for orthodontic treatment were collected. Measurements of cephalometric parameters of composite analysis were obtained with manual and smartphone application (OneCeph) method and compared statistically. Cephalometric tracing duration was also compared between two methods. Result: Cephalometric tracing duration using manual method was found to be significantly higher (p<.001) than that of the app method. There was no significant difference in values of SNA, SNB, ANB, Nasion perpendicular to point A, Nasion perpendicular to pogonion (pog), Angle of convexity, Go-GN/SN, FMA, U1–NA (degree), U1-NA (linear), L1–NB (degree), Cant of Occlusion, Interincisal angle, Nasolabial angle, Upper lip to Steiner’s S line, Lower lip to Steiner’s S line obtained with the manual and application method. The values of linear measurement between Lower incisor to NB line showed significant difference (p<0.05). Conclusion: Although there was no significant difference in cephalometric measurement, cephalometric tracing duration of cephalometric analysis using Smartphone application was significantly faster than that of conventional method.